2012
DOI: 10.1371/journal.pone.0039911
|View full text |Cite
|
Sign up to set email alerts
|

A FRET-Based High Throughput Screening Assay to Identify Inhibitors of Anthrax Protective Antigen Binding to Capillary Morphogenesis Gene 2 Protein

Abstract: Anti-angiogenic therapies are effective for the treatment of cancer, a variety of ocular diseases, and have potential benefits in cardiovascular disease, arthritis, and psoriasis. We have previously shown that anthrax protective antigen (PA), a non-pathogenic component of anthrax toxin, is an inhibitor of angiogenesis, apparently as a result of interaction with the cell surface receptors capillary morphogenesis gene 2 (CMG2) protein and tumor endothelial marker 8 (TEM8). Hence, molecules that bind the anthrax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…Further characterization of this hit demonstrated a complex inhibition curve and toxic effects upon administration in mice 19 , damping our enthusiasm for further study in the context of angiogenesis. However, during follow-up experiments at Clemson University we discovered that there were dramatic differences in the anti-CMG2 activity of separate lots of tannic acid, even though they were from the same supplier.…”
Section: Resultsmentioning
confidence: 91%
“…Further characterization of this hit demonstrated a complex inhibition curve and toxic effects upon administration in mice 19 , damping our enthusiasm for further study in the context of angiogenesis. However, during follow-up experiments at Clemson University we discovered that there were dramatic differences in the anti-CMG2 activity of separate lots of tannic acid, even though they were from the same supplier.…”
Section: Resultsmentioning
confidence: 91%
“…To confirm this conclusion, the authors tested cisplatin against two other toxins translocated by PA, the anthrax edema toxin and the cytotoxin FP59, a fusion of LF and exotoxin A from Pseudomonas aeruginosa , and demonstrated that cisplatin inhibited both toxins. Note that the cisplatin’s receptor-binding inhibitory properties were reported (57) as discussed earlier in present review. Interestingly, the administration of cisplatin-pretreated lethal doses of LT resulted in total protection of BALB/cJ mice and Fisher 344 rats, whereas the administration of cisplatin to mice before or after toxin administration was not protective.…”
Section: Pa Lf and Ef As Antitoxin Design Targetsmentioning
confidence: 55%
“…More recently, two pilot screen studies were reported where a sensitive high-throughput fluorescence resonance energy transfer (FRET) assay was used to identify potent small-molecule inhibitors of PA interaction with CMG2 (57) and TEM8 (58). The assay was based on FRET detected during the interaction of a fluorescently labeled CMG2 or TEM8 with a fluorescently labeled PA and allowed identification of tannic acid and cisplatin, and edselen and thimerosal as, respectively, CMG2/PA and TEM8/PA interaction inhibitors.…”
Section: Pa Lf and Ef As Antitoxin Design Targetsmentioning
confidence: 99%
“…Abovementioned advantages of KAR have thus made these tools amenable for high throughput [61] and led the kinase sensors to be cited as best biosensors in physiology [62]. …”
Section: Amenability Of Fret-based Biosensors For High Throughputmentioning
confidence: 99%